POVERTY, INCOME, AND EDUCATIONAL LEVEL: A CASE STUDY IN BERA DISTRICT, PAHANG, MALAYSIA (Journal of Economics and Sustainability, 2023)
Low levels of education and low income are often associated with communities located in rural areas. This is because rural communities have many constraints in obtaining education, employment opportunities, and earning a high income. This study aims to examine the factors that cause poverty in rural communities and investigate the socio-economic position and level of educational achievement of parents and children in rural communities in Bera District, Pahang, Malaysia. This study used a quantitative method for data collection. Questionnaires were administered to 100 respondents from the community living in the Bera district. Data obtained from respondents were analysed using Microsoft Excel and SPSS software through the Chi-square method. The study found that almost 51 percent of respondents agreed that the factors that drive poverty in rural families are the low education of household heads and the income earned by household heads based on their education level. In addition, a total of 59 respondents agreed with the issue of low education standards affecting the low level of income; 74 respondents agreed with the lack of employment opportunities in rural areas; and 59 respondents agreed that the education of the household heads makes it difficult for the children to get a good and higher education. As a result, the emphasis and opportunities on education, income, and employment opportunities, particularly in rural areas, must be increased more precisely.